Stanowisko Światowej Rady Kościołów w sprawie troski o naturalne środowisko - Płachciak, Adam (The Position of World Council of Churches and the address of John Paul II concerning the protection of the nature, 2008)
The following paper presents some selected events and documents of the World Council of Churches and the social science of John Paul II concerning the appearance of hazards of natural environment of people. The position of WCC and the address of John Paul II concerning natural environment care create favourable conditions for seeking solutions to some crucial world’s problems such as: justice, peace, sustainable development and present and future generations’ rights.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 81-91